Analisa Ergonomis Pemanfaatan Meja dan Sofa dari Limbah Ban Mobil - Diana Chandra Dewi (Universitas Batanghari Jambi, 2020)
The more the number of vehicles increases, the more problems that arise, for example air pollution from running engine activities and the amount of used tire waste from the vehicle. Waste from used tires can cause various serious problems if not handled properly. Used tires are waste that is harmful to the environment. This type of waste will be difficult to decompose by decomposing bacteria, this will be very dangerous for the environment. This study aims to analyze tables and sofas by utilizing car tire waste as the main raw material and in order to fulfill the ENASE aspect so that the tables and sofas made can be said to be ergonomic. The methods used in this study include qualitative and quantitative methods. Data processing techniques in this study used a comparison test and multiple linear regression test (ANOVA) to ensure relevant data. In the comparison test that has been done there are differences between all variables before and after and in the multiple linear regression test (ANOVA) that have been carried out there is no influence between the dependent variable and the independent variable.